1987
DOI: 10.1073/pnas.84.8.2256
|View full text |Cite
|
Sign up to set email alerts
|

Porphyrins are endogenous ligands for the mitochondrial (peripheral-type) benzodiazepine receptor.

Abstract: ABSTRACT"Peripheral-type" benzodiazepine receptors are localized to the outer mitochondrial membrane. We have identified potent competitive inhibitors of these receptors and purified them from human blood and from several rat organs. TLC analysis of the purified inhibitor from erythrocytes displays a single peak of inhibitory activity with an absorbance spectrum identical to hemin. All of the inhibitory activity in extracts of several tissues can be accounted for by their porphyrin and metalloporphyrin content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
1
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(199 citation statements)
references
References 28 publications
(35 reference statements)
4
191
1
3
Order By: Relevance
“…In support of the latter concept, porphyrin-derived photosensitizers may localize to and directly bind mitochondrial proteins such as the peripheral benzodiazepine receptor or the adenine nucleotide translocator. 35,36 Thus, it is most likely that PDT-induced SMC apoptosis is triggered at or near mitochondria. Further evidence of PDT acting on mitochondria is provided by the presence of the mitochondrial 7A6 antigen after PDT and release of AIF.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the latter concept, porphyrin-derived photosensitizers may localize to and directly bind mitochondrial proteins such as the peripheral benzodiazepine receptor or the adenine nucleotide translocator. 35,36 Thus, it is most likely that PDT-induced SMC apoptosis is triggered at or near mitochondria. Further evidence of PDT acting on mitochondria is provided by the presence of the mitochondrial 7A6 antigen after PDT and release of AIF.…”
Section: Discussionmentioning
confidence: 99%
“…Heme is also utilized in mitochondria for the synthesis of heme proteins. It has been reported that hemin and protoporphyrin IX bind to the peripheral-type benzodiazepine receptor (25,26) located in the mitochondrial outer membrane. As OGC is well conserved in yeast and human cells and localizes to the mitochondrial inner membrane (27), it may play an important role in the accumulation of endogenous porphyrin heme and the heme precursors in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Endogenous ligands for PBRs include protoporphyrin IX and a newly described cytoplasmic protein, PRAX-1, that specifically interacts with these receptors. 3,4 PBRs are involved in steroidogenesis, heme biosynthesis, immune and stress responses, cell growth, differentiation and mitochondrial respiratory control. 5 Recent data also suggest that PBR is structurally and functionally related to the Rhodobacter sphaeroides tryptophan-rich sensory protein (TspO).…”
Section: Introductionmentioning
confidence: 99%